Correlation of Electrophysiological Properties and Hearing Preservation in Cochlear Implant Patients. Issue 7 (August 2015) - Dalbert, Adrian; Sim, Jae Hoon; Gerig, Rahel; Pfiffner, Flurin; Roosli, Christof; Huber, Alexander
Abstract : Objective: To monitor changes in cochlear function during cochlear implantation using electrocochleography (ECoG) and to correlate changes to postoperative hearing preservation. Methods: ECoG responses to acoustic stimuli of 250, 500, and 1000 Hz were recorded during cochlear implantation. The recording electrode was placed on the promontory and stabilized to fix the position during cochlear implantation. Baseline recordings were obtained after completion of the posterior tympanotomy. Changes of the ongoing ECoG response at suprathreshold intensities were analyzed after full insertion of the cochlear implant electrode array. Audiometric tests were conducted before and 4 weeks after surgery and correlated with electrophysiological findings. Results: Ninety-five percent (18/19) of cochlear implant subjects had measurable ECoG responses. Under unchanged conditions, recordings showed a high repeatability without significant differences between 2 recordings ( p ⩽ 0.01). Ninety-four percent (17/18) of subjects showed no relevant changes in ECoG recordings after insertion of the cochlear implant electrode array. One subject showed decreases in responses at all frequencies indicative of cochlear trauma. This was associated with a complete hearing loss 4 weeks after surgery compared with mean presurgical low-frequency hearing of 78 dB HL. Conclusion: Extracochlear ECoG is a reliable tool to assess cochlear function during cochlear implantation. Moderate threshold shifts could be caused by postoperative mechanisms or minor cochlear trauma. Detectable changes in extracochlear ECoG recordings, indicating gross cochlear trauma, are probably predictive of complete loss of residual acoustic hearing.